The immunophilin FKBP12 inhibits hepcidin expression by binding the BMP type I receptor ALK2 in hepatocytes - Colucci, Silvia (Blood, 2017)
Visual Abstract Download figureOpen in new tabDownload powerpoint The expression of the key regulator of iron homeostasis hepcidin is activated by the BMP-SMAD pathway in response to iron and inflammation and among drugs, by rapamycin, which inhibits mTOR in complex with the immunophilin FKBP12. FKBP12 interacts with BMP type I receptors to avoid uncontrolled signaling. By pharmacologic and genetic studies, we identify FKBP12 as a novel hepcidin regulator. Sequestration of FKBP12 by rapamycin or tacrolimus activates hepcidin both in vitro and in murine hepatocytes. Acute tacrolimus treatment transiently increases hepcidin in wild-type mice. FKBP12 preferentially targets the BMP receptor ALK2. ALK2 mutants defective in binding FKBP12 increase hepcidin expression in a ligand-independent manner, through BMP-SMAD signaling. ALK2 free of FKBP12 becomes responsive to the noncanonical inflammatory ligand Activin A. Our results identify a novel hepcidin regulator and a potential therapeutic target to increase defective BMP signaling in disorders of low hepcidin.
Gesehen am 17.08.2018